Metallogenic evolution of uranium deposits in the Middle East and North Africa deposits. (February 2016) - Howari, Fares; Goodell, Philip; Salman, Abdulaty
Abstract: This paper is briefly involved in classification and distributions of the Middle East and North Africa (MENA) uranium deposits. The study of these mineral systems can significantly contribute to our further understanding of the metallogeny of known and poorly explored deposits. This provides contribution to, and further enhancement of, current classifications and metallogenic models of uranium systems, allowing researchers to emphasize on unknown or poorly studied mineral systems found in MENA. The present study identified eight metallogenic types of uranium associated with: 1) the Archean rocks and intra-cratonic basins, 2) the Pan-African granites and rhyolites which are characterized by igneous activity, 3) Phanerozoic (Paleozoic) clastics, these deposits are the sedimentological response to Pan African magmatism, 4) Mesozoic (basal) clastics type e.g. Nubia sandstones which are characterized by uranium minerals, 5) regional sedimentary phosphate deposits which are categorized as geosynclinal, or continental margin deposits, on the shelf of the Tethys Ocean, 6) Cenozoic Intracratonic Felsic Magmatism of the Tibesti and Hoggar, and the sandstone U deposits of adjoining Niger. These are similar to the Pan-African magmatism metallogenic, 7) Calcretes, and 8) Resistate minerals which are often enriched in rare earth elements, sometimes including uranium. They are thus sometimes considered as U resources but poorly explored in the MENA region. These metallogenic types are described and discussed in the current paper. Highlights: Poorly explored deposits were identified in the MENA region. Questions and knowledge gaps on uranium provenances in MENA were identified. Uranium deposits were classified in the MENA region. The sedimentological response of uranium deposits to Pan African magmatism were described. Nubia sandstones are characterized by uranium minerals but poorly studied.